Arduino based iot gardening system - Lok, Joey Jo Wei (2024)
This project relates to the trend of technology nowadays, the Internet of Things (IoT). The project title “Arduino Based IoT Gardening System” targets to utilize the IoT technology to improve gardening experience. By using Arduino and IoT technologies, an automated gardening solution is created to enable users to remotely oversee the environmental conditions of their garden. This project will utilize varieties of sensors to collect environmental data such as soil moisture sensor, temperature and humidity sensor, light intensity sensor, and the air quality sensor. The data collected will be processed and send to the users’ devices in graph form.The Arduino Based IoT Gardening System introduces a few innovative functions such as Automated Irrigation, Collection of Environmental Data and Notifications. The objective of the project is to improve plant care efficiency and to utilize the resources efficiently. This project emphasis on simplicity, allowing amateur or expert to use it easily to improve their gardening experience with technologies.This project mainly focusses on increasing the sustainability and utilizing the resources efficiently compared to the traditional gardening methods. On the other side, the use of Internet of Things (IoT) helps user to keep track on the environmental data remotely without having to physically observe their garden. This project provides beneficial contribution to the domains of automated gardening and smart gardens.